Global economic prospects : (World Bank, 2007)
Contents of the book is: Prospects for the Global economy; the coming Globalization; income distribution, inequality, and those left behind; new pressures in labor markets: integrating large emerging economies and the Global sourcing of service; managing the evironmental risks to growth.